2019
DOI: 10.1093/ageing/afz116
|View full text |Cite
|
Sign up to set email alerts
|

Successful ageing from old to very old: a longitudinal study of 12,432 women from Australia

Abstract: Objectives We examined the development of disease and disability in a large cohort of older women, the extent to which these conditions exempt them from being classified as successful agers and different trajectories of disease, disability and longevity across women’s later life. Methods We used survey data from 12,432 participants of the 1921–26 birth cohort of the Australian Longitudinal Study of Women’s Health from 1996 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Ascertainment of physical functioning outcomes was less complete as this was dependent on participation in the survey. Attrition rates for ALSWH are around 10% for each survey and have been reported elsewhere [30][31][32][33].…”
Section: Plos Onementioning
confidence: 73%
“…Ascertainment of physical functioning outcomes was less complete as this was dependent on participation in the survey. Attrition rates for ALSWH are around 10% for each survey and have been reported elsewhere [30][31][32][33].…”
Section: Plos Onementioning
confidence: 73%
“…Consequently, we were unable to measure the health status of those who did not participate in the subsequent surveys after the baseline survey. It is likely that these women had higher rates of morbidity (also observed in the current study) and potentially with more disease and disability problems [1]. Given that, the length of life with chronic disease but no disability and life with disability could be underestimated in our study.…”
Section: Table A1mentioning
confidence: 60%
“…There is a high probability that many older people will develop disease, they will live with disease for many years, and they are likely to develop disability and to live with disability for more years. An earlier study on this cohort identified a small proportion of women as 'successful agers' who had no disease and disability until their age 90-95 [1]. The Georgia aging study on centenarians also classified some small percentage of people as 'escapers' who have no disease and disability [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The later period of life can be associated with increasing burden of disease and disability, decline in physical function, decreased capacity for well-being and quality of life, reduced social participation and increased needs for health and social care. However, as shown by , Leigh (2017), and others, there is great heterogeneity of ageing experience, although many people will experience some decline in physical function as they age (14,15). Figure 1 shows the conceptual relationships between physical functioning, housing pathways, and the needs for care as people age (care pathways).…”
Section: A Conceptual Model For Housing and Carementioning
confidence: 98%